Altitude: Acclimatization to Intermediate Altitudes - Hallagan, L. F.; Pigman, E. (Sportscience)
The article deals with a) Physiologic Effects of Altitude Acclimatization and Exercise and b) Prevention and Treatment of Acute Mountain Sickness.